Evaluation of a Bitter Gourd protein isolate in a cookie formulation. Issue 5 (3rd September 2021) - Batool, Rizwana; Yasmin, Iqra; Munawar, Iqra; Aziz, Mahwash; Tehseen, Saima; Khan, Wahab Ali; Azam, Muhammad
ABSTRACT: Consumption of Bitter gourd ( Momordica charantia L) seed can provide vegetable protein for use in consumer products. Protein was extracted from defatted bitter gourd seed meal with isoelectric precipitation. Isolates were examined for protein content, recovery, yield, bulk density, water absorption capacities, oil absorption capacities, foaming and emulsifying properties. Wheat flour was replaced with protein isolate (up to 20%) to prepare blends and functional properties of blends determined, to develop protein-enriched cookies. Bitter gourd seed meal contained: crude protein (40.62 ± 0.68%), Mg (54.52 ± 1.06 mg/100 g), Ca (43.13 ± 1.13 mg/100 g), total phenolic content (5.06 ± 0.66 mg GAE∙g −1 ) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity of 30.98 ± 0.46%. Bitter gourd seed protein isolate supplemented cookies were evaluated for physical analysis, proximate composition and sensory characteristics. Maximum moisture (2.66 ± 0.04%), protein (18.67 ± 0.41%), fiber (0.89 ± 0.06%) and ash (0.93 ± 0.03%) contents were found in 20% substituted cookies. Cookies prepared with 15% substitution were most liked by panelists. The bitter gourd seed protein isolate can be used in various food products as a protein source.